2018
DOI: 10.1021/acs.jpca.7b10031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Kinetics and Mechanism of the Reaction of Chlorine Atoms with CH3CHClCH3 and CD3CDClCD3

Abstract: The overall rate constants for H-abstraction (k) from CHCHClCH and D-abstraction (k) from CDCDClCD by chlorine atoms in the temperature range 298-528.5 K were determined and are described by the expressions: k = (3.52 ± 0.21) × 10 exp(-184 ± 19/T) cm molecule s and k = (1.91 ± 0.16) × 10 exp(-185 ± 31/T) cm molecule s respectively. The results of the experiment show that the value of the kinetic isotope effect (k/k) for the overall rate constants is temperature independent and is equal to 1.85 ± 0.17. A theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
2
3
2
1
Order By: Relevance
“…Similar to reaction R1, reaction R2 had negative temperature dependency both experimentally and computationally over the studied temperature range, which is due to the formation of more stabilized prereactive complexes. Sarzynḱi et al 23 measured the rate coefficient for reaction R2 and observed a positive temperature dependency, which contradicts our reported results. They also have studies of reaction R2 using the RR method with ethane as reference.…”
Section: Relative Rate Measurements For 2-chloropropanecontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar to reaction R1, reaction R2 had negative temperature dependency both experimentally and computationally over the studied temperature range, which is due to the formation of more stabilized prereactive complexes. Sarzynḱi et al 23 measured the rate coefficient for reaction R2 and observed a positive temperature dependency, which contradicts our reported results. They also have studies of reaction R2 using the RR method with ethane as reference.…”
Section: Relative Rate Measurements For 2-chloropropanecontrasting
confidence: 99%
“…While the room temperature rate coefficients are in reasonable agreement with the present values, the positive temperature dependence may be attributed to any of the mentioned differences in the experimental conditions. Also, Sarzynḱi et al 23 theoretically explored the mechanism for the hydrogen abstraction of 2-CP by Cl atoms. In their investigation, they observed the rate coefficient for the abstraction of hydrogen attached to the secondary carbon to be decreasing with increase temperature.…”
Section: Relative Rate Measurements For 2-chloropropanementioning
confidence: 99%
See 1 more Smart Citation
“…at 296 K, Wallington et al 15 . at 295 K, and the temperature dependences of k H determined by Kumar and Rajakumar 16 in the temperature range of 263–363 K. For the studied reaction, we observed a positive temperature dependence which is not in line with the experimental temperature dependence of k H as determined by Kumar and Rajakumar 16 in the temperature range of 263–363 K. The same is true for the reaction of CH 3 CHClCH 3 + Cl 43 . We determined a positive temperature dependence in the temperature range of 298–528 K, while Kumar and Rajakumar 16 recorded the opposite temperature dependence in the temperature range of 263–363 K.…”
Section: Resultscontrasting
confidence: 65%
“…Conforme discussões na literatura, isto geralmente ocorre em reações que apresentam um pré-complexo (aqui representado por IM1) e quando o estado de transição correspondente apresenta energia menor que aquela dos reagentes. 87,88 Este fato justifica também a diminuição da constante de velocidade com o aumento de temperatura, o qual foi observado na Tabela 20. Para concluir, as energias de ativação envolvidas nas duas etapas da reação CH 4 + Au + → IM2 → AuCH 2 + + H 2 são de -19,4 e 66,0 kcal mol -1 , respectivamente.…”
Section: Resultados E Discussõesunclassified